The Impact of Implementation of Family‐Initiated Escalation of Care for the Deteriorating Patient in Hospital: A Systematic Review. Issue 4 (3rd June 2016) - Gill, Fenella J.; Leslie, Gavin D.; Marshall, Andrea P.
Abstract: Background: Rapid response systems incorporate concepts of early recognition of patient deterioration, prompt reporting, and response which result in escalation of patient care. The ability to initiate escalation of care is now being extended to families of hospitalized patients. Research Aims: To identify the impact of implementation of family‐initiated escalation of care for the deteriorating patient in hospital? Methods: A systematic review of peer‐reviewed publications was conducted. Databases were searched from January 2005 to May 2015 for articles reporting the implementation and evaluation of family involvement programs. Reference lists of retrieved articles were searched. Results: Ten articles (all descriptive studies) reported implementation and evaluation of response systems for patients and families to trigger an alert for help; five described a triaged response; five reported systems for families to directly activate the rapid response team. Five articles reported implementation in the pediatric setting. There were a total of 426 family‐initiated calls, range 0.17 to 11 per month, with no deaths reported. All calls were deemed to be appropriate and three calls resulted in intensive care unit admissions. The basis of patient‐ or family‐initiated calls stemmed from communication or systems breakdown. The large range in frequency of calls was associated with the process implemented, the strategies used and the calling criteria (up to four). Feedback from families was positive. There appeared to be a level of staff stress associated with introducing this process. Linking Evidence to Action: A variety of practice models and calling criteria were reported to either directly activate an existing rapid response team or trigger a separate response to patient‐ or family‐initiated calls. The broader calling criteria and more comprehensive implementation strategies were associated with more patient‐ and family‐initiated escalation of care calls. There is no systematically researched evidence to assess the value of family‐initiated calls for deteriorating patients.